Endorhizosphere of indigenous succulent halophytes: a valuable resource of plant growth promoting bacteria - Milica Dragojević; Nada Stankovic; Lidija Djokic; Vera Raičević; Jelena Jovičić-Petrović (Environmental Microbiome, 2023)
Abstract The adaptability of halophytes to increased soil salinity is related to complex rhizosphere interactions. In this study, an integrative approach, combining culture-independent and culture-dependent techniques was used to analyze the bacterial communities in the endorizosphere of indigenous succulent halophytes Salicornia europaea, Suaeda maritima, and Camphorosma annua from the natural salt marshes of Slano Kopovo (Serbia). The 16 S rDNA analyses gave, for the first time, an insight into the composition of the endophytic bacterial communities of S. maritima and C. annua. We have found that the composition of endophyte microbiomes in the same habitat is to some extent influenced by plant species. A cultivable portion of the halophyte microbiota was tested at different NaCl concentrations for the set of plant growth promoting (PGP) traits. Through the mining of indigenous halotolerant endophytes, we obtained a collection representing a core endophyte microbiome conferring desirable PGP traits. The majority (65%) of the selected strains belonged to the common halotolerant/halophilic genera Halomonas, Kushneria, and Halobacillus, with representatives exhibiting multiple PGP traits, and retaining beneficial traits in conditions of the increased salinity. The results suggest that the root endosphere of halophytes is a valuable source of PGP bacteria supporting plant growth and fitness in salt-affected soils.